Comparison of Mesenteric Lengthening Techniques in IPAA: An Anatomic and Angiographic Study on Fresh Cadavers. Issue 8 (August 2018) - İsmail, Erkin and Açar, Halil İbrahim and Arslan, Murat Nihat and Çoban, İsmail and Cömert, Ayhan and Aşlar, Ahmet Keşşaf and Kuzu, Mehmet Ayhan
Abstract : BACKGROUND: The IPAA technique restores anal functionality in patients who have had the large intestine and rectum removed; however, 1 of the most important reasons for pouch failure is tension on the anastomosis. OBJECTIVE: The aim of this study was to compare technical procedures for mesenteric lengthening used for IPAA to reduce this tension. DESIGN: After randomization, 4 different techniques for mesenteric lengthening were performed and compared on fresh cadavers. SETTING: This was a cross-sectional cadaveric study. MAIN OUTCOME MEASURES: In the first group (n = 5), stepladder incisions were made on the visceral peritoneum of the mesentery of the small intestine. In the second and third groups, the superior mesenteric pedicle was divided, whereas the ileocolic pedicle (n = 7) or marginal vessels (n = 6) were preserved during proctocolectomy. In the fourth group (n = 7), the superior mesenteric pedicle was cut without preserving any colic vessels. Mesenteric lengthening was analyzed. Angiography was performed to visualize the blood supply of the terminal ileum and pouch after mesenteric lengthening. RESULTS: Average mesenteric lengthening was 5.72 cm (± 1.68 cm) in group 1, 3.63 cm (± 1.75 cm) in group 2, 7.03 cm (± 3.47 cm) in group 3, and 7.29 cm (± 1.73 cm) in group 4 ( p = 0.011 for group 2 when compared with the others). LIMITATIONS: The study was limited by nature of being a cadaver study. CONCLUSIONS: Stepladder incisions through superior mesenteric pedicle trace are usually sufficient for mesenteric lengthening. In addition, division of the superior mesenteric pedicle with either a preserving marginal artery or without preserving ileocolic and marginal arteries leads to additional mesenteric lengthening. Abstract : Supplemental Digital Content is available in the text.